PERENCANAAN PEMBANGUNAN KEKUATAN MARITIM INDONESIA UNTUK MENGHADAPI TANTANGAN TAHUN 2020 - Wirasuta, Dadang Sobar (Jurnal Pertahanan & Bela Negara, 2013)
Problems of Indonesian maritime force development planning is inseparable from the role of government to support the development of maritime forces. In accordance with geography constellation as the largest archipelago in the world according to UNCLOS 1982, Indonesian economic development currently the largest in Southeast Asia and number 16 in the world with 6.4% gross domestic product (year on year). In this sense, it is time for implementing maritime force development based on maritime perspective and state defense as a whole integrated. Regardless of budget required by the military to implement its vision and mission of defense, the state has to be able to fulfill it and is able to offset foreign policy of the so-called Indo-pacific region in 2020. Keywords: Defense, Maritime Defense, Military Reformation, Military Innovation.